2003
DOI: 10.2165/00003495-200363170-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HMG-CoA Reductase Inhibitors on Coagulation and Fibrinolysis Processes

Abstract: Recent large clinical trials have demonstrated that HMG-CoA reductase inhibitors, or statins, markedly reduce morbidity and mortality when used in the primary and secondary prevention of cardiovascular disease. It has been established that the benefits of statin therapy in cardiovascular disease can be explained not only by the lipid-lowering potential of statins but also by nonlipid-related mechanisms (so-called "pleiotropic effects") that contribute to the positive effect of statins on the incidence of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 145 publications
5
135
2
3
Order By: Relevance
“…In line with our hypothesis, we observed the presence of correlations between baseline IGF-1 levels and baseline levels of triglycerides, HDL cholesterol, 2-hr post-challenge plasma glucose, HOMA-IR, FFA, uric acid, hsCRP and homocysteine. Because insulin resistance, atherogenic dyslipidaemia, low-grade inflammation and increased production of the remaining biomarkers assessed in our study are associated with the faster development and progression of atherosclerosis [21][22][23][24][25][26][27][28], the obtained results seem to be clinically relevant. Considering the complex pro-atherogenic effect of the markers studied, our results suggest that even moderately hyperprolactinaemic patients, particularly if this condition is secondary to a prolactin-secreting tumour, may be susceptible to the earlier development and accelerated progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 67%
“…In line with our hypothesis, we observed the presence of correlations between baseline IGF-1 levels and baseline levels of triglycerides, HDL cholesterol, 2-hr post-challenge plasma glucose, HOMA-IR, FFA, uric acid, hsCRP and homocysteine. Because insulin resistance, atherogenic dyslipidaemia, low-grade inflammation and increased production of the remaining biomarkers assessed in our study are associated with the faster development and progression of atherosclerosis [21][22][23][24][25][26][27][28], the obtained results seem to be clinically relevant. Considering the complex pro-atherogenic effect of the markers studied, our results suggest that even moderately hyperprolactinaemic patients, particularly if this condition is secondary to a prolactin-secreting tumour, may be susceptible to the earlier development and accelerated progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 67%
“…Fenofibrate prevented a testosteroneinduced decrease in HDL cholesterol, while testosterone prevented an unfavorable effect of fenofibrate on plasma homocysteine, attributed to an alteration in creatine-creatinine metabolism and/or changes in methyl transfer [27,28]. Taking into account that increased levels of the investigated variables are associated with the earlier development and accelerated progression of atherosclerosis-related disorders [29][30][31][32], men with LOH and atherogenic dyslipidemia may benefit the most from the combined treatment with oral testosterone undecanoate and micronized fenofibrate. It seems that this combined treatment is an interesting therapeutic option particularly in symptomatic males with metabolic syndrome and very low testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several experimental and clinical studies have shown that statins produced favorable effects on thrombotic parameters (24). Statins diminish procoagulant activity, which is observed at various stages of the coagulation cascade (25).…”
Section: Discussionmentioning
confidence: 99%